The representation of mental health sufferers in administrative and legal discourse - Marchese, Mariana Carolina (2017)
This article examines the records of mental incompetence cases filed at a court of the first instance in Buenos Aires Province, Argentina. Using a Critical Discourse Analysis framework and qualitative methods, we explore the ways in which mental health sufferers are represented. Applying Tone Theory and Appraisal Theory (attitude/judgement subsystem) to our data, we distinguish two discursive zones. In one of them, subjects are constructed with linguistic resources that amount to inscribed expressions of negative social judgement on their capacity. A discursive dichotomy is created whereby people are either competent or incompetent. In the other zone, these negative dichotomous judgements are largely softened by explicitly positive ones, without disappearing altogether. We suggest that mental incompetence, far from being a dichotomous concept, might be gradual.